Analisis Faktor-Faktor yang Mempengaruhi FDR Bank Umum Syariah (Studi Kasus PT Bank Muamalat Indonesia Tbk) - Hanafi Nugraha; Destian Arshad (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
The purpose of this study is to analyze factors that affect the liquidity capability of Islamic banks in Indonesia. One of the ratios which used to measure the ability of liquidity and to assess the financial performance of an Islamic bank is FDR. variables which used are ROA, CAR, NIM, and BI Rate. The data used in the study were secondary data on the quarterly financial statements of PT. Bank Muamalat Indonesia Tbk for the period 2012-2019. The research model or analysis tool used in this study is multiple linear regression analysis using statistical data processing applications. The results of this research are that the variables ROA, CAR, NIM, and BI Rate have a simultaneous effect on FDR and partially NIM and BI Rate have a significant effect on FDR, while ROA and CAR partially do not have a significant effect on FDR.